(untitled) (Journal of the College of Education for Women, 2019)
The present study aims at representing the importance of Quranic readings in the interpretation of the meaning of the Holly Quran in Imam Al Wahidi’s interpretation “Al Wasiet”, declaring its meaning, and eliminating of the paradox which takes place when trying to understand the intention of the Almighty Allah in His Holly book. The study aims at: 1- Defining the paradox linguistically and in terminology according to the formatives or the fundamentalists, the scientist of interpretation and of the Quranic sciences. 2-Reasoning paradox in the Quranic readings: Believing in matters that disagree with the Holly Quran and Sunnis, variety of the subjects in the verses, disagreement of the place and the place for the verses, the different phases informant, variety of the verb in verses, the prophetic effective verses on different circumstances, variety of the pronunciation, the allusion of paradox between the verse and the Hadeeth of the Prophet, the eccentricity of statements, disappearance of syntax, the paradox concerning the grammar and structure of words, the summary and shortness, hesitation of the meaning of the verse between the is opposing or agreed concept , and multitude of the readings in the verses and raising its paradox with explanatory examples.